Prevalency of Nematode in Bali Cattle at Manokwari Regency - Muhammad Junaidi; Priyo Sambodo; Dwi Nurhayati (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2014)
This study was conducted from August to October 2006, a disease caused by worms digestive tract is one of the causes of the decline in beef production . The purpose of this study was to assess the number of infected cattle nematode, the nematode types and amount of each type of nematodes in Bali cattle in Manokwari. Based onobservations on the worm eggs, total of 23 individuals (44.23 %) of Bali cattle ( puppies and adults ) infected with nematodes. Most of the infected cow is a cow that as many as 16 puppies cattle (69.56 %), while the remaining 7 animals (30.44 %) is the mother cow. Types of nematodes that infect cattle puppies and adult cattle are Cooperiasp., Bunostomum sp., Mecistocirrus sp. and Trichuris sp. The frequency of attacks in a row is as much as 13 cattle Cooperia sp, Mecistocirrus sp as many as 10 head of cattle, as many as 8 sp bunostomum cows and Trichuris sp. as much as 5 cows. The highest number of eggs in a row is Bunostomum sp. (1520), Cooperia sp. (1280), Mecistocirrus sp. ( 1200) and Trichuris sp. (280). The average number of eggs per gr feces ( EPG ) of 4 species of parasites that infect a row is Bunostomum sp . (190 EPG), Mecistocirrus sp. (120 EPG) Cooperia sp. (98.46 EPG)and Trichuris sp. (56 EPG). As many as 44.23 % of Bali cattle in three districts (Masni, Oransbari dan Prafi) attacked nematodes which are predominantly cattle aged less than one year .